Colonoscopy and sigmoidoscopy use among older adults in different countries: a systematic review - Chen, Chen; Brenner, Hermann (Preventive medicine, 2017)
Screening for colorectal cancer (CRC) by colonoscopy and sigmoidoscopy has been demonstrated to be effective in reducing CRC incidence and mortality, and they are increasingly employed as screening tests and for diagnostic purposes in many countries. We conducted a systematic review to provide up-to-date estimates on the utilization of lower gastrointestinal endoscopy (colonoscopy and sigmoidoscopy) in the general average-risk population in different countries. PubMed and Web of Science were searched for relevant articles published between 1 September 2008 and 31 October 2016. A total of 23 studies from the US and 20 studies from other countries were included in this review. Estimates from the US were highest, continued to increase over the past decade and reached 62% for colonoscopy use within 10 years in people aged 50-75 years in 2012. Endoscopy use in other countries was substantially lower (12-44% for lifetime colonoscopy use and 13-30% for recent colonoscopy use), except for Germany, where 55% of the screening-eligible population reported colonoscopy utilization within the previous 10years in 2008-2011. Both lifetime and recent endoscopy use increased with age and peaked at approximately 70-75 years. Although several European and Asian countries have started to collect endoscopy utilization data through periodic national health surveys, more data are still much needed from non-US countries. With the implementation of CRC screening programs in an increasing number of countries, especially European countries, an increase in endoscopy use and subsequent reduction in CRC incidence and mortality in the years to come might be expected in those countries.